Arthrocentesis Versus Rocabado Exercises on Temporomandibular Disc Displacement Without Reduction - Mohamed, Eman Shawkey; Othman, Eman Mohamed; Elmorsy, Khairy Abdelhamied; Abed Rashid, Nesrin Afify (Journal of Neonatal Surgery, 2025)
Background: Background: Temporomandibular joint disorders (TMD) are common, especially in females, causing pain and jaw dysfunction with significant impact on quality of life. Early diagnosis and effective management are essential to improve patient outcomes. Aim of the study: This study was designed to evaluate and compare the effects of the Rocabado exercise protocol and arthrocentesis in patients diagnosed with temporomandibular joint (TMJ) disc displacement without reduction. Methods: The study involved 68 patients with MRI-confirmed TMJ disc displacement without reduction, recruited from Qalyubia Governorate Hospitals with treatment sessions conducted between September 2022 and May 2024. Participants were randomly assigned to receive either arthrocentesis or an 8-week Rocabado exercise program. Pain and jaw movement were evaluated before and after treatment using the Visual Analogue Scale and Therabite Range of Motion scale. Results: The study and control groups (N=34 each) were comparable in gender (study: 22F/12M; control: 17F/17M; p=0.220), affected side (study: 47.1% left; control: 55.8% left; p=1.000), and age (48.24 ± 5.6 vs. 47.24 ± 5.27 years; p=1.000). Both groups showed significant improvements in right lateral excursion (study: 0.85 ± 0.61 to 1.29 ± 0.52 mm; control: 1.53 ± 0.79 to 2.24 ± 0.65 mm; p=0.001), left lateral excursion (study: 1.12 ± 0.91 to 1.71 ± 0.68 mm; control: 1.47 ± 0.99 to 2.06 ± 0.85 mm; p=0.001), and pain reduction measured by VAS (study: 4.93 ± 1.04 to 1.24 ± 0.88; control: 5.93 ± 1.04 to 1.0 ± 0.88; p=0.001). The control group demonstrated superior improvements in lateral excursion and pain reduction compared to the study group, indicating greater functional and symptomatic benefits post-intervention. Conclusion: This research fills a critical gap in the existing literature by providing evidence-based insights for clinicians in tailoring treatment strategies for TMD management. Future studies should explore long-term outcomes and patient satisfaction to further inform clinical practice. Both approaches have their merits; arthrocentesis is recommended for patients seeking rapid relief from pain and functional impairment, while Rocabado exercises are more suitable for long-term rehabilitation.